(3Ydhe GdCQV hGbJUGO GdHjFIs - (3SJjOgGe(B, (3QhfGdOs ((3GdbGgQI(B:s (3OGQ GdcJGH GdMOjK(B,s, 2008)
(3jVe GdEbJUGO hchcH GdCQV , YdGeGJ GdELgGO GdefGN hGdejGg, GdbGYOI GdHjhdhLjI, Tcd GbJUGO GdHjFI, HfGA GdEbJUGO GdTeSj GdEjOQhLjfj, GdJZPjI GdLOjOI ddLejY, MeGjI efJLGJ GdZGHGJ hNOeGJgG, EYGOI JUeje GdeOf dJdGFe GdfGS, JKHjJ YOO GdScGf Yf WQjb NaV GdNUhHI, COhGJ EYGOI gjcdI GdEbJUGO, GdESQGY aj YedjI GdEfJbGds
Keywords: (3GdEbJUGO GdJMdjdjs; (3GdHjFIs; (3Ydhe GdCQVs